Academic detailing - Shankar, PR; Jha, N; Piryani, RM; Bajracharya, O; Shrestha, R; Thapa, HS (Kathmandu University Medical Journal, 2010)
There are a number of sources available to prescribers to stay up to date about medicines. Prescribers in rural areas in developing countries however, may not able to access some of them. Interventions to improve prescribing can be educational, managerial, and regulatory or use a mix of strategies. Detailing by the pharmaceutical industry is widespread. Academic detailing (AD) has been classically seen as a form of continuing medical education in which a trained health professional such as a physician or pharmacist visits physicians in their offices to provide evidence-based information. Face-to-face sessions, preferably on an individual basis, clear educational and behavioural objectives, establishing credibility with respect to objectivity, stimulating physician interaction, use of concise graphic educational materials, highlighting key messages, and when possible, providing positive reinforcement of improved practices in follow-up visits can increase success of AD initiatives. AD is common in developed countries and certain examples have been cited in this review. In developing countries the authors have come across reports of AD in Pakistan, Sudan, Argentina and Uruguay, Bihar state in India, Zambia, Cuba, Indonesia and Mexico. AD had a consistent, small but potentially significant impact on prescribing practices. AD has much less resources at its command compared to the efforts by the industry. Steps have to be taken to formally start AD in Nepal and there may be specific hindering factors similar to those in other developing nations. Key words: Academic detailing; pharmaceutical industry; evidence-based information DOI: 10.3126/kumj.v8i1.3235 Kathmandu University Medical Journal (2010), Vol. 8, No. 1, Issue 29,126-134